Penerapan Metode Al Qiroah Untuk Meningkatkan Pemahaman Membaca Pada Pelajaran Bahasa Arab Di SMP: The Application of Al Qira’ah Method - muhammad singgih; Muhammad Irham (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2020)
This research is based on the poor ability of students to understand Arabic texts and the lack of interest in reading that is owned by students. So, the students have difficulty in understanding Arabic lessons. The problem in this research is